Data-driven Visual Graph Query Interface Construction and Maintenance: Challenges and Opportunities - Bhowmick, Sourav Saha (2017)
Visual query interfaces make it easy for scientists and other nonexpert users to query a data collection. Heretofore, visual query interfaces have been statically-constructed, independent of the data. In this paper we outline a vision of a different kind of interface, one that is built (in part) from the data. In our data-driven approach, the visual interface is dynamically constructed and maintained. A data-driven approach has many benefits such as reducing the cost in constructing and maintaining an interface, superior support for query formulation, and increased portability of the interface. We focus on graph databases, but our approach is applicable to several other kinds of databases such as JSON and XML.